2001
DOI: 10.1046/j.1471-4159.2001.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the phosphorylation of initiation factor eIF‐2α, elongation factor eEF‐2 and p70 S6 kinase after transient focal cerebral ischaemia in mice

Abstract: Mice were subjected to 60 min occlusion of the left middle cerebral artery (MCA) followed by 1±6 h of reperfusion. Tissue samples were taken from the MCA territory of both hemispheres to analyse ischaemia-induced changes in the phosphorylation of the initiation factor eIF-2a, the elongation factor eEF-2 and p70 S6 kinase by western blot analysis. Tissue sections from additional animals were taken to evaluate ischaemia-induced changes in global protein synthesis by autoradiography and changes in eIF-2a phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 50 publications
6
86
0
2
Order By: Relevance
“…CHOP expression is a representative feature of ER stress-induced cell death (Harding et al, 2000;Oyadomari et al, 2001); thus, our results strongly indicate that oxidative ER stress is involved in ischemic neuronal cell death. This is a novel finding because it is known that the upper stream of the ER stress response occurs after ischemia, but whether this is actually relevant to neuronal cell death is uncertain (Althausen et al, 2001;Kumar et al, 2001;Hayashi et al, 2003a, b). In both the ischemia models used in this study, neurons with a prominent induction of ATF-4 and CHOP underwent apoptosis, but those without it Figure 7 Change in the level of CHOP expression in mouse brains after transient focal ischemia.…”
Section: Discussionmentioning
confidence: 92%
“…CHOP expression is a representative feature of ER stress-induced cell death (Harding et al, 2000;Oyadomari et al, 2001); thus, our results strongly indicate that oxidative ER stress is involved in ischemic neuronal cell death. This is a novel finding because it is known that the upper stream of the ER stress response occurs after ischemia, but whether this is actually relevant to neuronal cell death is uncertain (Althausen et al, 2001;Kumar et al, 2001;Hayashi et al, 2003a, b). In both the ischemia models used in this study, neurons with a prominent induction of ATF-4 and CHOP underwent apoptosis, but those without it Figure 7 Change in the level of CHOP expression in mouse brains after transient focal ischemia.…”
Section: Discussionmentioning
confidence: 92%
“…Previous reports have demonstrated that the ER is involved in ischemic neuronal cell death, protein synthesis inhibition [37,38] , phosphorylation of phospho-extracellular signal-regulated kinase (PERK) [39] and eukaryotic initiation factor 2 alpha (eIF2α) [40] , depletion of the ER calcium pool [41] , accumulation of unfolded proteins in the ER [42] , and induction of the ER molecular chaperone [43] . An increasing number of studies indicates that autophagy is induced by ER stress in organisms from yeast to mammals [44,45] .…”
Section: Er Stress and Oxidative Stressmentioning
confidence: 99%
“…These data are consistent with previous reports that show no change in phosphorylation of eIF2a in cerebral ischemia. 10,13,34 As the 12 h ischemic samples are similar to the 6 h time points, this time point has been omitted from the remaining studies to be presented.…”
Section: Resultsmentioning
confidence: 99%
“…While initially surprising given reports of eIF2a phosphorylation in translational control of tissue culture cell hypoxia, 45 these results are consistent with previous reports in cerebral ischemia. [9][10][11]13 It is hypothesized that during ischemia, depletion of ATP is so severe that it may inactivate mechanisms that promote eIF2a phosphorylation. 11 It is widely accepted that eIF2a phosphorylation plays a significant role in translation inhibition during reperfusion, but this mechanism cannot account for suppression of protein synthesis during cerebral ischemia [9][10][11]13 or myocardial ischemia (as shown here).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation